AB0906 Ixekizumab improves fatigue in a subset of patients with psoriatic arthritis. (12th June 2018) - Orbai, A.-M.; Gladman, D.D.; Goto, H.; Birt, J.; Lin, C.-Y.; Kvien, T.K.
Abstract : Background: Psoriatic arthritis (PsA) is a chronic, systemic, inflammatory disease with both articular and extra-articular symptoms including joint pain, enthesitis, dactylitis, and fatigue. Fatigue is increasingly recognised as a priority symptom to patients and has been added to the PsA core set of outcomes for clinical trials. 1 The best instrument to assess fatigue has not yet been defined. Objectives: To assess fatigue improvement following treatment with ixekizumab (IXE), an anti-interleukin (IL)−17A monoclonal antibody, relative to placebo (PBO) in PsA patients. Methods: In two phase 3 randomised controlled trials, patients naïve to and experienced with biologic disease-modifying antirheumatic drugs (SPIRIT-P1, SPIRIT-P2, respectively) received subcutaneous PBO, ADA 40 mg every 2 weeks (SPIRIT-P1 only; reference arm), or IXE 80 mg every 2 weeks (Q2W) or every 4 weeks (Q4W) after a 160 mg starting dose for up to 24 weeks. At Week 16, all patients considered inadequate responders (IR) received rescue therapy. PBO and ADA patients were re-randomised (1:1) to Q2W or Q4W at Week 16 (IR) or Week 24; ADA patients underwent a washout prior to IXE treatment. Patients rated their worst level of fatigue during the past 24 hours at baseline, Week 4, 12, 16, 24, 32, and 52 on the 11-point Fatigue Severity Numeric Rating Scale (Fatigue NRS; not yet validated) where 0=no fatigue and 10=as bad as you can imagine. The minimal clinically important difference (MCID) was defined as an improvement ≥3 on the Fatigue NRS. Results: At Week 24 significantly more patients in both studies achieved fatigue improvements≥3 on the Fatigue NRS with both IXE doses versus PBO (table 1; NRI). When evaluating group level changes, statistically significant improvements on the Fatigue NRS were observed with both IXE doses versus PBO prior to Week 24 in both studies. At Week 24, significance was observed in the SPIRIT-P2 study only (table 1; MMRM). For patients who continued IXE treatment beyond Week 24, mean improvements on the Fatigue NRS persisted through Week 52 (table 1; MI). Conclusions: In a subset of PsA patients, clinically meaningful improvements in fatigue level were observed following IXE treatment. Fatigue improvement persisted with up to 1 year of IXE treatment. Reference: [1] Orbai, et al. Ann Rheum Dis. 2017;76:673–80. Disclosure of Interest: A.-M. Orbai Grant/research support from: Abbvie, Celgene, Eli Lilly, Horizon, Janssen, Novartis, Pfizer, Consultant for: Eli Lilly, Janssen, Novartis, Pfizer, UCB, D. D. Gladman Grant/research support from: Abbvie, Amgen, Celgene, Janssen, Novartis, Pfizer, UCB, Consultant for: Abbvie, Amgen, BMS, Celgene, Eli Lilly, Janssen, Novartis, Pfizer, UCB, H. Goto Grant/research support from: Abbvie, Eli Lilly, Kyowa Hakko Kirin, Consultant for: Abbvie, AYUMI, Chugai, Eisai, Eli Lilly, Janssen, Maruho, Mitsubishi Tanabe, Novartis, Pfizer, Takeda, Speakers bureau: Abbvie, AYUMI, Chugai, Eisai, Eli Lilly, Janssen, Maruho, Mitsubishi Tanabe, Novartis, Pfizer, Takeda, J. Birt Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, C.-Y. Lin Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, T. K. Kvien Grant/research support from: AbbVie, BMS, MSD, Pfizer, Roche, UCB, Consultant for: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celgene, Celltrion, Eli Lilly and Company, Epirus, Hospira, Merck-Serono, MSD, Mundipharma, Novartis, Oktal, Orion Pharma, Hospira/Pfizer, Roche, Sandoz, UCB